Conscience network : a chronicle of resistance to a dictatorship - Sugata Srinivasaraju (Gurugram : Vintage / Penguin Random House India, 2025)
"This is a parallel history of resistance to Indira Gandhi$1 (Bs dictatorial rule between 1975 and 1977, when an internal emergency was proclaimed in India. The events here unfold entirely in the United States of America surrounded by the echoes of emergency action in India. The book has an intimate historiographic style and is narrated through the lives, actions and world views of chosen protagonists, who with perseverance and principle constructed a classic Gandhian movement. The book not only tracks political developments, ideological debates and sociocultural contexts of the time but also records how American pacifists, Quakers, civil rights activists, academics, authors, senators and Congressmen came together in solidarity to form a network of conscience to save India$1 (Bs democracy. Amid this, a quiet thread in the book is the story of the Indian diaspora in the US that had just about begun staring at a horizon of influence. It is widely believed that one of the factors that pushed Indira Gandhi to end the Emergency in 1977 and call for a general election was international pressure. Being Jawaharlal Nehru$1 (Bs daughter, it is said that she was sensitive to how she was being perceived overseas, and after a point, thought it was counterproductive to play dictator. However, this book does not get into such conjectures or presumptions but endeavours to paint a true and complex picture of the time. The narrative here is fused with a diligent study of personal papers and archival material in India and overseas that had neither been accessed or assessed till now. This is yet another offering from an author whose books have been applauded for their uncommon insights, intellectual bandwidth and a fine literary style."s
Keywords: Civil rights--India; Political rights--India; India--Politics and government; Internal security; National emergency